BANKING FRAUD: A CONCEPTUAL FRAMEWORK OF DREDGING UP VARIOUS BANKING SCAMS, CAUSES AND PREVENTIVE ROLE OF LAW ENFORCEMENT AGENCIES - Arvinder Kaur, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Indian banking system is witnessing various financial scandals & scam. Hardly had we just moved on ourselves from one scam very soon the new one rumble on the floor. Perpetrators are responsible for vulnerability of financial system and exponential rise of NPA, stressed asset and rigorous impact on profitability. Anomaly is prevalent in banking sector due to lack of stringent rules & its implementation. Driven from frail technology, complex legal regulations and procedures, the early detection and prevention of fraud turns crucial. This perspectives study focuses on three broad areas consist of firstly literature review, secondly comprehensive analysis of banking extortions including the types of deceits, reasons, detection measures and thirdly legislative and regulatory framework for curbing this menace.